Injection ranitidine induced death - Anandhi, S.; Mani, R. (International Journal of Basic & Clinical Pharmacology, 2020)
Ranitidine is a histamine-2-receptor antagonist. It was a commonly used drug. It holds excellent safety record. Anaphylactic reactions to ranitidine is uncommonly encountered. Death due to ranitidine is extremely a rare event and very few cases are reported world-wide. Clinical history, Lab investigations and histological data of a 43-Years old woman with negative history of allergic events, who died suddenly after the intra-venous administration of 50mg of intravenous ranitidine which was prescribed as a routine pre medication prior hysterectomy is presented below. Though the incidence of anaphylactic reactions is less with ranitidine, precautions to be taken prior administration of the drug and when such an event is encountered it should be promptly managed.